(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the analysis of the problem of the development of communicative and organizing abilities of the individual in the period of maturation. It is proved that the development of communication skills is a prerequisite for successful socialization. The author notes that the application of the model of advanced education for sustainable development allows to fill the system of educational and educational influence with personal meaning. In the plane of this, the features of the development of the communicative and organizing abilities of adolescent schoolchildren are analyzed. The conclusion is made about the need for targeted support of this process in the context of sustainable development education.